Worldviews, Virtues, and Education - Bert Meeuwsen (Theology and Philosophy of Education)
Meaning-oriented Reflection (i.e. ‘MORe3.1.2’) is addressed as modus operandi for reflecting on ethical behaviour. The article connects decolonising the curriculum, worldviews core virtues, educational interventions, while ensuring a safe learning environment. Critical thinking, based on normative rationales, allowing educational design research concepts, is focal. Four alternative interventions, using MORe3.1.2 with admitting decolonised differing descriptions of a bonded network of six core virtues, provide answer. Ideas for further research are suggested.